Vegetation responses to snow cover removal and rainfall reduction in subalpine grasslands: Insights from a 4-year field experiment in the Spanish Pyrenees - Antonio I. Arroyo; Miguel Castillo-Garcia; Yolanda Pueyo; Concepción L. Alados (Arctic, Antarctic, and Alpine Research)
Reduced precipitation as well as warming may result in less snow accumulation in seasonally snow-covered areas, leading to lower minimum soil temperatures and more frequent and severe soil frosts. Therefore, plant stress is increased not only by drought in warmer months, but also by increased exposure to frost in cooler periods. We conducted a 4-year field experiment to evaluate the effects of diminished snowpack accumulation (through snow removal) and rainfall reduction (through rain-out shelters) on aboveground plant productivity, diversity and species composition of two subalpine grassland plant communities from the central region of the Spanish Pyrenees. We found that the snow removal treatment decreased minimum soil temperature by 0.5°C. Plant diversity decreased by 16 percent, although this effect was only observed in one of the grasslands studied. Aboveground primary productivity seemed to be unaffected. In contrast, we found that the rainfall reduction treatment negatively affected aboveground productivity of leguminous forb species, yet no effect on plant diversity was observed. Both treatments were important drivers of changes in plant species composition. Overall, our results suggest that the resilience of subalpine grasslands to snow cover removal and rainfall reduction treatments may depend on the specific community composition and dominant plant groups.